Rehabilitation of scapular dyskinesis: from the office worker to the elite overhead athlete. Issue 8 (18th May 2013) - Cools, Ann M J; Struyf, Filip; De Mey, Kristof; Maenhout, Annelies; Castelein, Birgit; Cagnie, Barbara
Abstract : The scapula functions as a bridge between the shoulder complex and the cervical spine and plays a very important role in providing both mobility and stability of the neck/shoulder region. The association between abnormal scapular positions and motions and glenohumeral joint pathology has been well established in the literature, whereas studies investigating the relationship between neck pain and scapular dysfunction have only recently begun to emerge. Although several authors have emphasised the relevance of restoring normal scapular kinematics through exercise and manual therapy techniques, overall scapular rehabilitation guidelines decent for both patients with shoulder pain as well as patients with neck problems are lacking. The purpose of this paper is to provide a science-based clinical reasoning algorithm with practical guidelines for the rehabilitation of scapular dyskinesis in patients with chronic complaints in the upper quadrant.